Maternal and foetal outcome in women with neurological disorders - Thomas, Daphne Rose; R., Beenakumari; V., Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Wide spectrums of neurological disorders are observed in pregnancy and puerparium. These disorders can alter the course of pregnancy and pregnancy can worsen them. Methods: This was a cross sectional observational study which included 154 patients in pregnancy and postpartum up to 6 weeks with neurological disorders admitted in department of obstetrics and gynecology, Government Medical College, Kottayam over a period of one year from December 2017. All patients underwent detailed general and systemic examination and were assessed by neurologist. After delivery maternal and foetal outcome and morbidity and mortality were observed. Results: Out of total 5202 deliveries, 154 patients presented in pregnancy and puerparium with neurological disorders amounting to 2.96 %. The age of patients ranged from 18-44. The commonest neurological disorder was epilepsy (60.4%). Other disorders were eclampsia (7.8%), cerebrovascular disorders (9.1%), brain tumors (4.5%), cranial nerve palsy (3.2%) and different types of other neurological disorders (14.9%). The most common presentation was generalized tonic clonic seizures (82.8%). 76.6% of patients had normal vaginal delivery and 13% underwent caesarean section. There were 5 cases of intrauterine death (3.2%), 5 cases of foetal anomalies (3.2%) and 3 cases of neonatal deaths (1.9%). One case of maternal mortality was there due to intra-cerebral hemorhhage. Conclusions: Epilepsy was the commonest disorder with good maternal and foetal outcome. Vascular disorders and eclampsia were associated with higher maternal and foetal morbidity and mortality.